Measurement and simulation of strain fields around crack tips under mixed-mode fatigue loading - Y. Hos; M. Vormwald; J.L.F. Freire (Fracture and Structural Integrity)
For various configurations examined in a series of fatigue experiments on thin-walled tubes under tension and torsion, the experimental results – crack path, crack growth life, near crack tip deformations, and crack closure – are measured and compared to the results of some numerical simulations. Partially automated optical inspection and the digital image correlation technique were used in the experimental investigation. In the finite element analyses, an actual geometry of a cracked structure has been modeled. The mechanical material behavior has been assumed as linear elastic in a first approach for calculating stress intensity factors. The nonlinear nature of the cyclic deformation has been taken into account by applying a cyclic plasticity model, and plasticity-induced crack closure is captured by a contact formulation.